Unraveling transfer pricing in construction sectors: Tax optimization, compliance, and environmental risk - Rahmat, Radhi Abdul Halim; Ramdhany, Muhamad Arief; Hendayana, Yana; Novatiani, Ait (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study highlights the consequence of tax optimization, regulatory compliance, and environmental risk index on the likelihood of transfer pricing in Indonesia's property, real estate, and building construction sectors. This study adopts a quantitative research approach, analyzing data from 19 companies in the property, real estate, and building construction sectors listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021 (76 observations). This study contributes novelty by employing binary logistic regression to investigate the interaction of tax optimization, regulatory compliance, and environmental risk index on transfer pricing in Indonesia's property, real estate, and building construction sectors, providing valuable insights into the determinants of transfer pricing practices in these industries. The research employs multiple linear and binary logistic regression to examine the influence of tax optimization, regulatory compliance, and environmental risk index on transfer pricing likelihood. - Tax optimization and regulatory compliance significantly impact the likelihood of Transfer Pricing in the property, real estate, and building construction sectors in Indonesia. However, the interaction between tax optimization and the environmental risk index does not significantly influence transfer pricing likelihood. In contrast, the interaction between regulatory compliance and the environmental risk index does have a significant positive effect. The implications are that tax optimization may subtly influence transfer pricing in the studied sectors. Maintaining regulatory compliance appears to act as a deterrent, and a favorable environmental risk index may encourage transfer pricing practices in Indonesia's property, real estate, and building construction industries.